Guidelines for engagement and good membership behavior of personnel organizations in Metta Pracharak Hospital (WatRaiKhing) - Anchaleeumnuyporn, Pattaraporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purposes of this research were to: 1) study the level of organizational commitment and good citizenship behavior of personnel; 2) compare the level of organizational commitment and good citizenship behavior of personnel, as classified by personal factors; 3) study the factors affecting organizational commitment and good citizenship behavior of personnel; and 4) study the guideline for building organizational commitment and good citizenship behavior of personnel. The research sample was 234 personnel of all types derived by proportional stratified random sampling, and 6 key informants derived by purposive sampling. The research instruments were a questionnaires and an in-depth interview constructed by the researcher. Data were analyzed with frequency, percentage, mean, standard deviation, independent t-test, one-way ANOVA, correlation analysis, stepwise multiple regression and content analysis. The research results were as follows: 1. The organizational commitment was at a moderate level (3.27), and the good citizenship behavior was at a high level (3.68) 2. The personnel with differences in gender and type of position had different level of organizational commitment and good citizenship behavior with statistical significance of .05. 3. All aspects of organizational commitment, which were basic needs, administrative support, relationship, and career advancement, affected organizational commitment building. The organizational commitment in aspects of relationship and career advancement affected good citizenship behavior. 4. The guidelines for building organizational commitment and good citizenship behavior of personnel were: in factors affecting organizational commitment, organizations should encourage, support and develop career advancement by giving opportunities for personnel to participate in training, seminars or study visit. The organization should organize meeting between executives and personnel to inform policy and receive personnel’s suggestions. Therefore, the meeting develops a good communication, recognizes problems and finds effective solutions about compensation and benefits. In organizational commitment building, organizations should consider about fair and equitable compensation and benefits. The performance appraisal process should be fair and transparent. Organization values and good organizational culture should be instilled. In good citizenship behavior aspect, organizations should build personnel’s awareness about living according to royal principles of sufficiency economy philosophy. The organization should promote job security. The executives should regularly monitor worksite to recognize problems and find solution guidelines systematically, and build good relationship among subordinates. Article history : Received 8 August 2017 Revised 28 September 2017 Accepted 1 October 2017 SIMILARITY INDEX = 0.00